Salinas artificiais como habitat alternativo para aves limícolas Charadriiformes: sazonalidade e uso do habitat no estuário Apodi-Mossoró, RN, Brasil - Elias, Anyelle Paiva Rocha (Universidade Federal Rural do Semi-Árido, 2017)
The increasing degradation of natural wetlands has led many shorebirds populations to use alternative or complementary habitats. The artificial salines are one of the most common alternative habitats used by shorebird to feed and rest in coastal areas. The aim of this study was to investigate the richness, composition, habitat use and seasonal variation of shorebirds species associated with the artificial salines of the Apodi-Mossoró Estuary, Brazilian semiarid. Between August 2012 and July 2016, fortnightly shorebirds Charadriiformes censuses were conducted (2 h duration) in an area of 145 ha of saline from this Estuary (04°57’S; 37°08’O), in periods of high and low tide. A cumulative total of 28,868 records of individuals of 19 species Charadriiformes were obtained during 192 censuses. The number of records of shorebirds per census in the summer (2nd fortnight of August to the first fortnight of March: 167.9 ± 16.9 records, mean ± SE, N = 112 censuses) was similar to that sighted in the winter (2nd fortnight of March to the 1st fortnight of August: 125.7 ± 11.4, N = 80) (U = 4221; p = 0.495). In the summer period, the number of shorebirds records per census did not vary between periods of high tide and low tide (U = 1280; p = 0.094). On the other hand, in the winter, the number of shorebird records at high tide was higher than at low tide (U = 501.5; p = 0.004). Comparing the use of microhabitats over the studied saline area, shorebirds were more frequent in the evaporation ponds (85% of total records), and less frequent in pumping (9%) and crystallization (6%) ponds. There was a significant difference in the number of records of individuals/ha (density), with the highest density of individuals per census in the evaporation ponds (H = 246; p < 0.0001). The evaporation and pumping ponds were used mainly for foraging (respectively 79% and 76% of the records by microhabitat) and the crystallization pond for resting (75%). Our results shows that the Apodi-Mossoró Estuary may be recognized as an important area for the conservation of migratory and resident Charadriiformes populations in the South America. The use of artificial salines of this Estuary by shorebirds as alternative habitats for feeding and resting makes important to implement a continuous environmental monitoring program in the salines in order to ensure the maintenance of species-specific ecological requirements and to avoid chemical contamination of these animals
Artificial saline as alternative habitat for shorebirds Charadriiformes: seasonality and habitat use in estuary Apodi-Mossoró, RN, Brazil
Keywords: Área de invernagem; Conservação da avifauna; Habitats alternativos; Migração; Semiárido; Wintering area; Bird conservation; Alternative habitats; Migration; Semiarid; CIENCIAS BIOLOGICAS::ECOLOGIA